Survey to assess the perception of veterinary medicine students on the didactic strategies received in their professional training at a private university in Lima - Peru. - Rondón Herz, Rodrigo (2021)
The objective of the study was to construct and validate a pilot survey to measure the perception of veterinary medicine students about the didactic strategies received in their professional training at the Peruvian University of Applied Sciences in Lima-Peru. The type of study was observational, descriptive and correlation’s. The instrument evaluated the dimensions of the didactic strategies variable (teaching perception, cognitive, procedural and attitudinal). Likewise, this questionnaire received content validation through the judgment of three experts, and was applied to 30 students to verify the wording of the items. It was then applied to a sample of 137 students. The internal reliability was defined through the determination of the Cronbach Alpha Coefficient (CAC) Overall (0.87) and for each item. In addition, the relevance of the application of the Exploratory Factor Analysis (EFA) was determined through the determination of the Kaiser Meyer Olkin Index (KMO= 0.65). Principal Component Analysis and the sedimentation plot were performed to determine the number of factors to be extracted. The PCA determined that there are specific questions that are correlated both for each indicator of each of the dimensions of the variable didactic strategies and for each of the five factors extracted. In addition, the CAC determined by factor showed an acceptable (0.66) to high (0.88) level of internal consistency, and the organization of the factorial structure with varimax rotation made it possible to identify the indicators per dimension that can be measured for each of the factors. Thus, the dimensions measured by factor are: 1) Teacher and procedure perception; 2) Teacher perception, cognitive and attitudinal; 3) Teacher and attitude perception; and 4) Cognitive and procedural.